Microleakage of class v cavities restored with flowable composite materials - Janković Ognjenka; Arbutina Adrijana; Knežević Nataša; Arbutina Radmila (Serbian Medical Society - Dental Section, Belgrade, 2014)
Introduction. Increasing requirements for durable fillings and marginal integrity have influenced the development of new materials and restorative techniques. Contemporary demands for esthetic restorations have encouraged the development of new composite material "self-etch flowable composite". The aim of this study was to test the marginal seal in small Class V cavities after restoration with self etch flowable composite material Vertise Flow and flowable composite Tetric Flow, both polymerised using conventional light-curing technique. Material and Methods. The study was conducted on 40 extracted human teeth (20 intact, 20 carious). Each group included 10 premolars and 10 molars. In all teeth two cavities class V of diameter 3×2×2 mm were prepared (buccal and lingual surface). On the buccal surface the cavities were filled with self etch flowable composite Vertise Flow (Kerr Dental Products), and on the lingual surface with flowable composite Tetric Flow (Ivoclar Vivadent) using appropriate adhesive system. Polymerisation was performed using LED lamp (Ivoclar Vivadent). Microleakage was tested with silver nitrate solution. Using stereoloupe with micrometer scale and six times magnification dye penetration was measured. Results. Mean dye penetration in intact molars restored with Vertise Flow was 3.41 μm, while in intact molars restored with Tetric Flow it was 4.23 μm. In intact premolars restored with Vertise Flow, the average dye penetration was 1.14 μm and in intact premolars restored with Tetric Flow it was 3.90 μm. Dye penetration in carious molars restored with Vertise Flow and polymerised using conventional polymerization technique was 3.66 μm, while using Tetric Flow it was 7.94 μm. In carious premolars restored with Vertise Flow dye penetration was 3.97 μm, while with Tetric Flow it was 7.12 μm. The total dye penetration was lower in intact compared to carious teeth. Greater dye penetration was found in molars compared to premolars. Conclusion. Vertise Flow showed better quality of bond with hard dental tissue than Tetric Flow when classical polymerization technique was used.